Development of a Solution Method to Promote Proper Bandaging Techniques for Transfemoral Amputees - Lalla, Bhaveen (Department of Human Biology, 2022)
Post-operative care for lower limb amputees focuses on reducing swelling and promoting healing of the residual limb. Healing and desired residual limb maturation is necessary to achieve a conical shape suitable for prosthesis integration. Elastic bandaging is applied to the residual limb to achieve this conical shape. Bandaging requires skill and frequent reapplication. In many cases, the amputee is unable to bandage the residual limb effectively following surgery and professional assistance may not be readily available, increasing the risk of permanent damage due to improper bandaging. Transfemoral amputees are often confined to a wheelchair and spend the most time without a prosthesis fitted compared to any other lower limb amputee. An effective method in achieving the optimum residual limb shape, while promoting proper bandaging is therefore required. The aim of this study was to develop a solution method to assist transfemoral amputees with proper bandaging to achieve a shorter healing period and promote faster prosthesis integration through residual limb re-shaping. An overall solution method comprising of three sub-systems was designed to instruct bandaging. This included the development of a bandaging template, a mobile application and an elastic bandage dispenser. A printable bandaging template generated by a Python script based on the measurements of the patient's residual limb circumferences was developed to instruct bandaging. Development of a mobile application allowed for the design of an interface to control the dispensing device and instruct bandaging steps. The developed Bandage Utility Dispenser (BUD) transmits unrolled bandage length measurements to the mobile application using Bluetooth, to meet the target bandage lengths. Target bandage lengths are calculated by a second Python script to recommend sufficient bandage lengths. Target bandage lengths are expected to apply adequate pressure, while covering the exposed area of the residual limb for the current bandaging step. Testing occurred on an anatomically correct residual limb model (ACM) and five constructed models (CM) assembled by altering proximal and distal ACM circumferential measurements in increments of 5 cm. Measurement and pressure testing were performed after successfully validating the use of the CMs using a Bland-Altman analysis on the ACM and a CM of equal dimensions. Measurement testing utilised a chi-square goodness of fit test to compare observed and expected bandage length measurements for each model. Results for all models indicated that observed and expected measurements did not differ significantly. Pressure testing was performed by measuring the pressure application along the perimeter of the models with assembled pressure pads. Readings were analysed using a one sample t-test to compare differences between sample means and the recommended pressure application from literature. Testing results indicated that pressure application for five of the six models were in an acceptable range. Future recommendations have been established to potentially improve design, functionality and testing of the current iteration of the BUD solution method.